Prevalence and Predictors of HIV Disclosure to Adult Family Members: A Cross-Sectional Survey Among People Living with HIV in South Africa - Simbayi, Leickness C.; Mabaso, Musawenkosi LH; Cloete, Allanise (Journal of Psychology and Psychotherapy Research, 2021)
Disclosure in the context of HIV is the sharing of information about one’s HIV-positive status, and many factors influence the decision to do so. This study examined the prevalence and predictors of HIV disclosure to adult family members using data collected from the South African 2014 People Living with HIV (PLHIV) Stigma Index. A purposive sample consisting of 10 473 PLHIV were recruited into the study from 18 districts across all of the nine provinces (two districts per province) out of a total of 52 districts found in South Africa. All respondents were linked to an institution for PLHIV accessing support or care related to HIV. Bivariate and multivariate logistic regression models were used to assess the association between HIV disclosure to family members and selected explanatory variables. A large majority (85°§1%) of the 9874 PLHIV who responded to the question on disclosure to adult family members reported that they had done so. Significant positive predictors of HIV disclosure to adult family members included reporting an age between 25 - 49 years [OR=1°§5: 95% CI (1°§2-1°§8), p<0.001], aged 50 years and older [OR=1°§5: 95% °§CI (1°§1 - 2°§0), p=0012], unemployment [OR=1°§3: 95% CI (1°§1 - 1°§5), p=0.002] and living with HIV for 5 and more years [OR=1°§6: 95% CI (1°§2 - 2°§0), p<.0.001]. On the other hand, significant negative predictors of disclosure included HIV testing decision taken under pressure from others [OR=0.6: 95% CI (0.5-0.8), p<0.001], testing without own knowledge [OR=0.3: 95% CI (0.2-0.5), p<0.001], only receiving pre-test HIV counselling [OR=0.4: 95% CI (0.3-0.5), p<0.001], and not receiving any counselling when testing for HIV [OR=0.6: 95% CI (0.4-0.9), p=0.012]. Overall, the majority of study participants had disclosed their HIV positive status to family members. However, there is a need to equip younger PLHIV and those who were recently diagnosed with HIV with the necessary positive coping mechanisms and self-esteem strategies in order to facilitate disclosure among this population group. Involuntary or forced HIV testing and poor/lack of pre- and post-test counselling should be discouraged since they have been shown to have negative consequences for disclosure.